Prevalence and correlates of severe anxiety in patients with first hospitalization for major depressive disorder combined with dyslipidemia: a large sample cross-sectional study - Yin, Huimin; Zhang, Qi; Li, Yi; Ma, Jun (Frontiers in Psychiatry, 2024)
Background: Anxiety symptoms and dyslipidemia are common co-morbidities in patients with major depressive disorder (MDD), and there are complex pathophysiologic as well as clinical mechanisms underlying the association between the three. In this study, we investigated the prevalence and associated factors of severe anxiety in first-time hospitalized patients with MDD with dyslipidemia. Methods: We included 708 patients with major depressive disorder with comorbid dyslipidemia and collected their sociodemographic and general clinical data as well as biochemical parameters such as lipids, thyroid function, and blood glucose. We also completed the Hamilton Anxiety Scale (HAMA), Hamilton Depression Scale (HAMD), Positive Symptom Scale (PSS), and Clinical General Impression Scale (CGI) to assess their clinical symptoms. Results: The prevalence of severe anxiety disorder was 11.02% in patients with MDD with comorbid dyslipidemia. Suicidal history, female gender, body mass index (BMI), HAMD score, PSS score, and FT4 level were risk factors for the development of severe anxiety symptoms. Higher HAMD scores, higher PSS scores, and suicidal history were influential factors in exacerbating severe anxiety symptoms. Conclusion: This study reports and identifies the prevalence of severe anxiety symptoms in first-time hospitalized MDD patients with dyslipidemia, as well as risk factors for anxiety symptoms and factors influencing their severity, and these identified factors may be potentially helpful and informative in preventing and intervening in severe anxiety disorders in this target population. Keywords: Dyslipidemia; Major depressive disorder; Severe anxiety; First hospitalization; Prevalence.